PENGARUH KEPEMILIKAN MANAJERIAL, KEPEMILIKAN INSTITUSIONAL, KOMISARIS INDEPENDEN, KOMITE AUDIT DAN KUALITAS AUDIT TERHADAP INTEGRITAS LAPORAN KEUANGAN (Studi Empiris Pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Periode 2014-2016) - Ulfa Puji Utami, 13.05.52.0114; Maryono, Maryono (Students Journal of Accounting and Banking, 2017)
This reseach aimed to analyze the influence of Managerial Ownership, Institutional Ownership, Independent Commissioner, Audit Committee and Quality Audit Integrity Financial Statements Against the Manufacturing Companies Listed on the Stock Exchange Period 2014-2016. The population in this study are all Manufacturing Companies Listed on the Stock Exchange Period 2014-2016. The sample selection using purposive sampling method. The analytical tool used in this research is multiple linear regression analysis. Statistical test results showed that the F-Test Managerial Ownership, Institutional Ownership, Independent Commissioner, Audit Committee and Quality Audit together influential Against Integrity Financial Statements.And the result of hypothesis testing partially indicate that Managerial Ownership, Audit Committee and Audit Quality have positive Influence not significant to Integrity of Financial Statement. Institutional ownership has no significant negative effect on Financial Statement Integrity. While Independent Commissioner has a significant negative effect on Financial Statement Integrity.Keywords: Integrity Financial Statements, Managerial Ownership, Institutional Ownership, Independent Commissioner, Audit Committee and Audit Quality